Inokulan Rhizobakteri untuk Meningkatkan Kelimpahan Mikroba Tanah, Klorofil dan Pertumbuhan Bibit Kelapa Sawit pada Inceptisols - Tualar Simarmata; Maria Eprina Kusumo Wardani; Eka Dwi Anggrainy (Fakultas Pertanian Universitas Padjadjaran, 2020)
Inorganic fertilizers are used intensively as the main source of essential nutrients to boost oil palms productivity. However, it’s also to contribute to degradation of organic matter and soil health. The research aimed to investigate the effect of rhizobacteria inoculant to increase the beneficial soil microbes (RNF= rhizobacteria nitrogen fixer and rhizobacteria phosphate solubilizes = RPS) in rhizobiome and the growth oil palm seedling was conducted from January to May 2020 on Inceptisols. The experiment was arranged as randomized block design, consisted of 9 treatments (control, 3, 6, 9, 12 kg ha-1 of RNF, and its combination with RPS and provided with 3 replicans. Observed respond were total bacteria, RNF, the seedling growth and chlorophyll content. The experimental results revealed that rhizobacterial inoculation had a significant effect on RNF, RPS, total bacterial population, and the chlorophyll content of oil palm seedlings. The abundance of soils microbes during the trial were rellative high (>108 CFU g-1). Inoculation of 3 kg ha-1 of rhizobacteria (RNF and RPS) increased the population of RNF to 4.02 x 108 CFU g-1. The highest of chlorophyll content (56.96 CCI) was obtained by the application 12 kg ha-1 of RNF, followed by applying of 3 kg and 9 kg of inoculant consortia (RFN + RPS), but not different significantly with the control. Results finding confirms that the application rhizocateria inoculant (RNF and its combination with RPS) could use to enhance the abundance of microbes in rhizobiome for supporting the growth of oil palm seedling